Urban Waste and Public Services: Survey Findings on Waste Management in Ciputat Market Area, South Tangerang City - Mukhamad Busro Asmuni; Deanda Dewindaru; , Ade Indriani Siagian; Hendika Dwinanda Wicaksana; Agnes Monica Marpaung (Jurnal Ragam Pengabdian, 2026)
Urban waste management is an environmental issue that directly impacts the comfort and quality of life of the community, particularly in market areas. The Ciputat Market area in South Tangerang City previously experienced significant waste accumulation, which disrupted daily activities and triggered public criticism of the local government. This study aims to analyze the level of community satisfaction regarding urban waste management in the Ciputat Market area. This research employs a quantitative descriptive approach using a survey method involving 100 respondents, comprising market vendors, visitors, local residents, and road users. Data were collected through a five-point Likert scale questionnaire and analyzed using descriptive statistics. The findings reveal that community satisfaction falls within the moderate to low category, with 62.5% of respondents expressing dissatisfaction or being less than satisfied with the waste management. The aspects receiving the lowest evaluations include the consistency of waste transportation and the sustainability of waste management policies. This condition reflects the suboptimal quality of public servis in waste management. Therefore, this study recommends that the state or local government must demonstrate a tangible presence through the reinforcement of strict policies and regulations. Furthermore, the government needs to act as a catalyst in fostering the active participation of citizens and the involvement of the private sector to develop a collaborative and sustainable waste management system.